Nyaya Vartika Tatparya: Tika of Vachaspati Mišra, Anantalal Thakur - Venkatakrishna, B V (Journal of Dharma, 1996)
Nyaya Vartika - Tatparya - Tika of Vachaspati Mišra, Anantalal Thakur, (ed), Delhi : Indian Council of Philosophic Research, 1996, pp. xii + 410